2014
DOI: 10.1590/0102-311x00073713
|View full text |Cite
|
Sign up to set email alerts
|

Sub-relato da ingestão energética e fatores associados em estudo de base populacional

Abstract: Objetivou-se identificar a prevalência de sub-relato da ingestão energética e os fatores associados em amostra de 331 indivíduos, proveniente do estudo de base populacional Inquérito de Saúde no Município de São Paulo, Brasil. A ingestão energética foi avaliada pela média de dois recordatórios de 24 horas coletados em dias não consecutivos. O gasto energético total foi calculado por equação preditiva, considerando sub-relatores os indivíduos com ingestão energética inferior a 2 desvios-padrão da razão ingestão… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 15 publications
0
9
1
8
Order By: Relevance
“…This bias is frequently observed in population studies about food intake 42 , particularly among women and overweight individuals 43,44,45 , but found no grounds in our study, since we did not find an association in the reporting of fruits and vegetables consumption by overweight women (OR = 1.06; 95%CI: 0.82-1.38), which weakens this possibility.…”
Section: S152contrasting
confidence: 76%
“…This bias is frequently observed in population studies about food intake 42 , particularly among women and overweight individuals 43,44,45 , but found no grounds in our study, since we did not find an association in the reporting of fruits and vegetables consumption by overweight women (OR = 1.06; 95%CI: 0.82-1.38), which weakens this possibility.…”
Section: S152contrasting
confidence: 76%
“…A prevalência dessa, por sua vez, observada neste trabalho (11,9%), foi também similar a outros que utilizaram a mesma metodologia para sua detecção e para avaliação do consumo alimentar, como o de Avelino et al 23 , que apontou prevalência de 15,1%, e o de McCrory et al 20 , que encontrou 11% de notificação imprecisa (não houve especificação de sub ou supernotificação, porém destacou-se que a grande maioria desse valor correspondia à subnotificação). No entanto, foi inferior à encontrada em outros trabalhos [24][25][26] .…”
Section: Discussionunclassified
“…Esse parâ-metro, comumente está atrelado ao descontentamento com a imagem corporal e ao desejo de ajuste social, que favorecem uma resposta mais aceitável socialmente 23,27 . Rasmussem et al 11 ain- da encontraram associação com a tentativa de comer de forma mais saudável e a preocupação com o peso corporal.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Studies that estimate energy intake have found a high prevalence of underreporting in individuals assessed in outpatient clinics, especially those with excess weight 24,25 . Thus, underreporting seems to be associated with obesity, the perceived need to restrict energy intake, and the desire for social adjustment.…”
Section: Discussionmentioning
confidence: 99%